KONSEP KETELADANAN DALAM SURAT AL-AHZAB AYAT 21 SEBAGAI METODE PENDIDIKAN ISLAM - Azis, Taufik Burhanudin (STAI Syubbanul Wathon Magelang, 2024)
To achieve educational goals, an ideal teaching and learning process is needed and an appropriate method is needed to achieve educational goals. This illustrates that method is an important factor in carrying out a teaching and learning process activity. In this way, the author questions what is the concept of the exemplary method according to Islamic Education? What is the interpretation by the interpreters of the Al-Qur'an Surah Al-Ahzab verse 21. The aim of this research is to find out the concept of theexemplary method which is the right way to use as a method in the Islamic education process. The data found shows that the uswah (exemplary) method is an applicable-practical method, a combination of theoretical and practical, a harmony between words and deeds, in its application it is directly in contact with life behavior. Thus it can be concluded that the uswah (exemplary) method contained in Q.S. Al-Ahzab verse 21 is a method which in its use or implementation uses uswah (example) which can be highlighted by an educator so that students can quickly and easily understand the material being taught.